PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN LITERASI SAINS PADA MATERI HUBUNGAN MAKANAN DENGAN KESEHATAN - Astuti, Rina; Sujana, Atep; Hanifah, Nurdinah (Jurnal Pena Ilmiah, 2017)
Problem Based Learning to Improve Science Literacy on Food Relation with Health. Science literacy is ability to review a problem or phenomenon on the point of science view. Science literacy can be enhanced trough the problem-solving process in science learning. Teacher roles as the information center, transforms into facilitator, motivator and creator to help construct student knowledge. Problem based learning process allows students to be actively involved because  given the opportunity to solve a problem related to an event.. Problem-based learning affects both the science literacy students of class V on the relationship of food to health. This is evidenced by the research using pre-experiment method with pretest-postest one group design which shows that problem-based learning can significantly increase students literacy ability in high, medium and low group. Based on the results of the study problem-based learning can be used as a solution to improve literacy skills of elementary school students.